KEBIJAKAN INDONESIA MENGELUARKAN ROADMAP VISION 4000 PEACEKEEPERS 2015-2019 PADA UN-PKO (UNITED NATION – PEACEKEEPING OPERATION) - Yossy Dwi Apriyanti; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This paper is an analysis of the foreign policy issued by Indonesia in increasing the number of troops to 4000 troops. This research focused on analyzing internal and external factors that influence Indonesia in issuing this policy. Indonesia is listed as a member of the United Nations which is very active in maintaining world peace, while there are countries that choose to abstain and just enjoy the peace created.The theoretical framework used in this study is the Neo-Realist perspective, the level of analysis of the nation-state, foreign policy theory. This study uses qualitative research by collecting data from reports and documents, books, legislation, online media and publications with primary sources from the Ministry of Foreign Affairs and the Ministry of Defense. The results of this study indicate that, in issuing policies, the state has many considerations that must be considered. The policy of sending 4000 troops issued by Indonesia also takes into account internal and external factors. Internal factors consist of government structure, security and national attributes. Meanwhile, external factors consist of the system structure, public opinion, global and regional problems in the private sector Keywords: Peacekeeping Forces, UNPKO, Mission, Policy, Vision Roadmap